LA LINGÜÍSTICA DEL PODER ORGANIZACIONAL EN EL CONTEXTO EDUCATIVO (De la Crítica, 2023)
The purpose of this essay is to review various studies on the linguistics of power and its influence in the educational context, to discover how language is used to establish and maintain power structures within organizations, and how linguistic strategies can be used to question or resist these organizational power dynamics. In addition, to understand how linguistics can generate more effective communication and collaboration within organizations, considering the works of the following authors: Tannen, Foucault, Bourdieu and Goffman, who will finally demonstrate the positive and negative influence of communication on organizations in the educational context, since this generates identity in the person and describes the philosophical nature of the organization. Therefore, it is evident how the linguistics of organizational power in educational contexts is used to establish a hierarchy of authority, facilitate or hinder the flow of information and communication, and how language to create an environment of trust and respect among the members of the organization motivating the achievement of institutional objectives.